# Generalized binomial theorem

Prove that: $$(1+x)^{\alpha}=\sum_{n=0}^{+\infty}{\alpha \choose n} x^n$$ for $x\in[0;1), \alpha \in\mathbb{R}$ based on Taylor's theorem with Lagrange remainder.

I don't feel such proofs. Isn't it kind of.. obvious? That when we expand $(1+x)^{\alpha}$ into series we get right side? I really want to understand this.

• It is not obvious. Tim Gowers says that "obvious" means "a proof comes immediately to mind". Does a proof of this statement come immediately to your mind? If so, what is it? – MJD Mar 25 '12 at 15:35
• You're right, it's not obvious. I thought when we expand $(1+x)^{\alpha}$ we got the right side, but apparently I don't understand it well.. so how to approach this? – xan Mar 25 '12 at 15:35
• Have you tried using the hint? What happens if you expand $(1+x)^\alpha$ with Taylor series? – MJD Mar 25 '12 at 15:36
• I've tried this way: $f(x)=\sum_{k=0}^{n}\frac{f^{(k)}(x_0)}{k!}(x-x_0)^k + R_n(x,x_0)$, so we have $f(x)=(1+x)^{\alpha}$ and expanding in $x_0=0$ we get $(1+x)^{\alpha}=1+\frac{\alpha(1+x)^{\alpha-1}}{1}x+\frac{\alpha(\alpha-1)(1+x)^{\alpha-2}}{2}x^2+...$ and it is exactly $\sum_n {\alpha \choose n}x^n$ I think.. where's the catch? :-) – xan Mar 25 '12 at 15:46
• You had a reasonable start, but then the coefficient calculation is not correct. Differentiate. The derivatives are $\alpha(1+x)^{\alpha-1}$, $\alpha(\alpha-1)(1+x)^{\alpha-2}$, and so on. You must evaluate these derivatives at $x=0$ (and divide by suitable factorial) to get the coefficients. So the $(1+x)^{\alpha-1}$ that you have should be replaced by $1$. – André Nicolas Mar 25 '12 at 20:09

You have that if

$$y=(1+x)^\alpha$$

then

$$y'(0)=\alpha$$ $$y''(0)=\alpha(\alpha-1)$$ $$\cdots=\cdots$$ $$y^{(n)}(0)=\alpha(\alpha-1)\cdots(\alpha-n+1)$$

$$y^{(n)}(0)=\frac{\alpha!}{(\alpha-n)!}$$

You can prove this last generalization by induction on $n$. The last equation is written for the sake of "order", but if you're not comfortable with it, you can use the $\Gamma$ function to denote the factorials.

Then

$$\mathcal{T}_k(y,0)=\sum\limits_{n=0}^k \frac{\alpha!}{(\alpha-n)!}\frac{x^n}{n!}$$

Then using the binomial coefficient notation

$$\mathcal{T}_k(y,0)=\sum\limits_{n=0}^k {\alpha \choose n}x^n$$

What you need now is that the series converges for $|x|<1$.

In my opinion you can argue as follows:

Fix $x$. Then the series

$$\lim\limits_{k \to \infty} \mathcal{T}_k(y,0)=\sum\limits_{n=0}^\infty {\alpha \choose n}x^n$$

will converge when

$$\lim\limits_{n \to \infty} \left|\frac{{\alpha \choose n+1}}{{\alpha \choose n}}\frac{x^{n+1}}{x^n}\right|<1$$

$$\lim\limits_{n \to \infty} \left|\frac{{n+1}}{n-\alpha}x\right|<1$$

$$\left|x\right|<1$$

ADD: Here's a part of an answer to a similar question:

Assume

$${\left( {1 + x} \right)^{\alpha}} = \sum\limits_{k = 0}^\infty {{a_k}{x^k}}$$

Since if two series \eqalign{ & \sum {{a_k}{{\left( {x - a} \right)}^k}} \cr & \sum {{b_k}{{\left( {x - a} \right)}^k}} \cr}

sum up to the same function then

$${a_k} = {b_k} = \frac{{{f^{\left( k \right)}}\left( a \right)}}{{k!}}$$

for every $k \leq 0$, we can assume:

$$a_k = \dfrac{f^{(k)}(0)}{k!}$$

Putting $y = {\left( {1 + x} \right)^{\alpha}}$ we get

$$y'(0) = \alpha$$ $$y''(0) = \alpha(\alpha-1)$$ $$y'''(0) = \alpha(\alpha-1)(\alpha-2)$$ $$y^{{IV}}(0) = \alpha(\alpha-1)(\alpha-2)(\alpha-3)$$

We can prove in general that

$$y^{(k)}= \alpha(\alpha-1)\cdots(\alpha-k+1)$$

or put in terms of factorials

$$y^{(k)}(0)= \frac{\alpha!}{(\alpha-k)!}$$

This makes

$$a_k = \frac{\alpha!}{k!(\alpha-k)!}$$

which is what we wanted.

$${\left( {1 + x} \right)^\alpha } = \sum\limits_{k = 0}^\infty {\alpha \choose k} {{x^k}}$$

You can prove this in a more rigorous manner by differential equations:

1. Set $f(x) = \displaystyle \sum\limits_{k = 0}^\infty {\alpha \choose k} {{x^k}}$ and prove the radius of convergence is 1.
2. Show that $f(x)$ is the solution to the ODE $$y' - \frac{\alpha }{{x + 1}}y = 0$$ with initial condition $f(0)=1$.
3. By the theorem that the solution to the linear equation

$$y'+P(x)y=R(x)$$

with initial conditions $f(a) = b$ is unique, you can prove the assertion. (prove that $y = {\left( {1 + x} \right)^{\alpha}}$ also satifies the equation and you're done.)

• @Downvoter Any feedback? What is the issue? – Pedro Tamaroff Mar 25 '12 at 23:49
• What is the definition of/which function is denoted $\mathcal{T}_k$? – Milosz Wielondek Apr 23 '12 at 22:03
• I see it now. Am I correct to assume $\mathcal{T}_k(y,n)$ is the taylor series of $y$ around $n$ of $k$th degree? – Milosz Wielondek Apr 23 '12 at 22:18
• @Milosz Yes, you are! However, note it is a polynomial, not a series. A series has "infinite" degree. – Pedro Tamaroff Apr 24 '12 at 11:48
• BTW, shouldn't the limit as given by OP, in fact be $x\in(0;1]$ since $0^0$ is undef. and for $x=1$ the equation ($2^a=\displaystyle\sum^{\infty}_{n=0}{\binom{a}{n}}$) is still true? – Milosz Wielondek Apr 27 '12 at 0:25